Synthesis and characterization of silver-chitosan nanoparticles on textile - Mehravani, Behnaz (2021)
Metal nanoparticles these times have gathered huge popularity in the fields of health industry. This study focuses on synthesis of silver and chitosan nanoparticles and study their antibacterial effects and cytotoxicity when they are coated on a fabric. The prepared fabric was subjected to characterization techniques such as XPS, XRD, EDX and SEM. These tests confirmed the presence of silver nanoparticles on the surface of the fabric. Antibacterial and cytotoxicity tests were conducted, and the results exhibited that silver nanoparticles have showed good antibacterial effect on both gram positive and gram-negative bacteria and showed no cytotoxicity. The antibacterial effect was effective after 10 cycles of washing.